Observations on Salmonella contamination of commercial duck farms before and after cleaning and disinfection. Issue 2 (4th March 2017) - Martelli, Francesca; Gosling, Rebecca J; Callaby, Rebecca; Davies, Rob
ABSTRACT: In the European Union, statutory control of Salmonella is in place in the chicken and turkey sectors, but not in the duck sector. In this study, 14 Salmonella- positive duck farms were sampled before and after cleaning and disinfection, and once the houses had been restocked with a new flock. The cleaning and disinfection programmes used were subdivided into two main categories: ones in which a final formaldehyde disinfection step was included (1) and ones in which it was not included (2). Several types of samples were collected during the study, and faecal samples were those more frequently positive (62% of faecal samples were positive for Salmonella in comparison to 2–23% of samples from all the other sample categories) ( P < 0.001). Independently of the cleaning and disinfection programme used, there was a statistically significant ( P < 0.001) reduction in the percentage of Salmonella -positive samples between before cleaning and disinfection (41.1%) and after cleaning and disinfection (3.1%). After restocking, the number of Salmonella -positive samples increased significantly ( P < 0.001), with 65.3% of the samples tested being positive for Salmonella . Farms in which disinfection programme 1 was used were 5.34 times less likely to have samples positive for Salmonella after cleaning and disinfection than farms which implemented programme 2. Formaldehyde acts effectively against Salmonella even in the presence of some residual organic matter. Limited residual contamination on farms after cleaning and disinfection represents a risk of infection for young ducklings, and thorough cleaning and disinfection procedures should be implemented to reduce the carry-over of infection between flocks.